Development of Animated Video of Graha Maria Annai Velangkanni Spiritual Tourism Object in Medan - Royal Januari Naibaho (Asian Journal of Applied Education (AJAE), 2024)
The purpose of this study was to make an animated video about Graha Maria Annai Velangkanni in Medan using Sparkol-Videoscribe by applying a 4-D creation model from Thiagarajan. The steps of this model are: (i) definition phase, (ii) planning phase, (iii) creation phase and (iv) deployment phase. Brochures, the official website of Graha Maria Annai Velangkanni Medan and interviews with Sr Angelina are used as data sources. This research was conducted at the Language Laboratory, Faculty of Languages and Arts, State University of Medan. The result of this production is an animated video made with Sparkol-Videoscribe. This video is 09:43 minutes long and is 388 megabytes long. This video is published on YouTube with https://youtu.be/AZ4Mw96mfrQ?feature=shared link and validated by material experts and media experts. The validator gave a score of 87.5 (good) to the material. Overall, the video received a score of 85.71 which was categorized as good by media experts. Therefore, it can be concluded that the animated video about Graha Maria Annai Velangkanni in Medan is valid and valid.